The Effect of Print-Rich Classroom Environment on Developing Kindergarten Children’s Awarenes of Written Language - Ihmeideh, Fathi (Jordan Journal of Educational Sciences, 2009)
This study aimed at investigating the effect of printrich classroom environment on developing kindergarten children’s awareness of the written language as compared to traditional environment. The study sample consisted of (88) kindergarten children. The sample was divided into two groups, the experimental group with (47) children taught in a print-rich classroom environment and the control group with (41) children taught in a traditional environment with no print materials. Results revealed statistical significant difference (α = 0.05) in the written language awareness test between the two groups in favour of the experimental group. The results also indicated that there was significant difference attributed to gender in favour of females. In addition, the results revealed no statistical significant difference attributed to the interaction between gender and group. In light of the study findings, the researcher suggests a number of recommendations for improving print-rich environments at kindergarten classrooms.